Reactivation of Hepatitis B Virus Associated with Chemotherapy and Immunosuppressive Agent - Indra Wijaya; Irsan Hasan (Acta Medica Indonesiana, 2013)
Hepatitis B virus (HBV) reactivation after chemotherapy or immunosuppressive therapy is a serious cause of liver-related morbidity and mortality. The mechanism of HBV reactivation is still unclear, but it is believed due to the suppression of immune response hence increasing the viral load. No uniform diagnostic criteria are available, HBV reactivation can be confirmed by an increase in serum HBV-DNA level. There are many consensus regarding this issue, including the type and duration of nucleoside analogue therapy which need to be understood as not all chronic hepatitis B patients will lead to HBV reactivation. Recently, there has been an increased awareness of reactivation of occult hepatitis B virus, especially in hepatitis B virus endemic area, including Indonesia as part of Asia Pacific region. Preempative antiviral therapy was the best approach to prevent the HBV reactivation.